(untitled) - Kreitner, Robert (New York, 2007)
Comprising several case studies, this Kreitner and Kinicki book gives you a thorough understanding of the concepts. Moreover, the internet exercises in this Kreitner and Kinicki book encourage students to enhance their problem-solving skills. This book on personnel management even comprises research on cross-cultural communication, self-monitoring, emotions, postmodern organizations, and the eight steps for leading change. Key topics covered in 'Organizational Behavior' by Kreitner/Kinicki include diversity in organizations, ethics, and globalization.
Keywords: Hành vi tổ chức,Organization behavior